Puzzle: Comic Crowds : Lost Ball - Haasteren, Jan Van (Newton, MA : CEACO, 2021)
Johannes (Jan) Van Haasteren was born in 1936 In a small town near Rotterdam, Holland. As soon as Jan began to hold a pencil, he became hooked on drawing. He attended the Academy of Arts in Rotterdam for drawing and the Academy of Arts to study publicity and advertising. When he was asked to co-produce a comic strip, his world of comic strip drawing began. In the 1980S, along with his career in poster illustration, Jan began illustrating images for the Dutch toy company, jumbo, which continues to this day. Still going strong at age 73, Jan is in his attic Studio daily, drawing the puzzle images which we proudly produce.